A Corpus-based Approach to the Compilation, Analysis, and Translation of Rural Tourism Terms - Fijo León, María; Fuentes Luque, Adrián (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
This paper describes an empirical, corpus-based analysis of the terms related to rural tourism accommodation establishments in three languages – Spanish, English, and French. The main objective is to identify and describe common characteristics shared by the concepts and the terms designating them in these languages, with the aim of suggesting the most suitable translation equivalents. The study is based on a computerized corpus divided into three comparable subcorpora. The results obtained from the analysis have direct implications for the translation of rural tourism texts.